Pengaruh Seleksi, Penempatan Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Intervening: (Studi Pada Perusahaan Daerah Air Minum Muara Tirta Gorontalo) - Totok Bachtiar Chairul Saleh; Moh. Rolli Paramata; Deby R. Karundeng; Yakup Yakup (Pusdikra Publishing, 2023)
The aim of the study was to analyze the effect of selection, placement and work environment on employee performance with motivation as an intervention variabel (Study at Muara Tirta Gorontalo Water Company). The data used in this study is primary data sourced from filling out questionnaires. The research population is 127 respondents using the census method. The analysis technique used to answer research problems and test hypotheses is path analysis with the help of Statistical Product Service Solution (SPSS) and Lisrel ver. 8.7 The findings of this study are (1) the interaction has a positive and significant direct effect on employee motivation, (2) placement has a positive and direct significant effect on employee motivation, (3) the work environment has a positive and direct significant effect on motivation employee work, (4) placement has a direct positive and significant effect on employee performance, (5) placement has a positive and direct significant effect on employee performance, (6) work environment has a positive and direct significant effect on employee performance, ( 7) work motivation has a direct positive and significant effect on employee work performance, (8) selection has a positive and direct significant effect on employee performance through work motivation, (9) placement has a direct positive and significant effect on employee performance through work motivation, ( 10) the work environment has a positive and significant direct effect on employee work performance through work motivation.